EVALUATING FACTORS TO AFFECT THE AGRICULTURAL PRODUCT EXPORT FROM VIETNAM TO CHINA, BASED ON THE “ONE BELT, ONE ROAD INITIATIVE” – THE APPLICATION OF GRAVITY MODEL - Thi Huong, Nguyen; Wang, HongShu; Nho Quyet, Tran; Quang Yen, Tran; Thi Thanh Hien, Nguyen (Journal of Forestry Science and Technology, 2021)
Agriculture is of paramount importance industry which spreads the most and reaches close connection to other industries. Within decades, China has been known as a country with a population of billions and being in high demand for agricultural products. Apart from the above reasons, the geographical position of China is also a great cause for Viet Nam to focus on China’s export market towards selling agricultural products. Viet Nam has such a great honor to partake in the “One belt, one road initiative” (BRI), our research team grabbed a chance to find out factors that affect the agricultural export of Vietnam to China. To identify and evaluate those factors, the research team has used the gravity model as the chief method. The research’s outcome indicated that Gross Domestic Product (GDP), geographical distance, economic gap, the population of China, the level of economic openness, inflation, agricultural land area are principal factors creating the effect on Vietnam’s agricultural export. Besides, not only does the initiative “One belt, one road” have a certain significance for improving transports and communications as well as infrastructure but it also receives maximum support from the Government of China. Taking part in the initiative “One belt, one road” also helps both countries approach more policies that are profitable.